Feature and Performance Comparison of the V-REP, Gazebo and ARGoS Robot Simulators - Pitonakova, Lenka; Giuliani, Manuel; Pipe, Anthony; Winfield, Alan (Towards Autonomous Robotic Systems, 2018)
In this paper, the characteristics and performance of three open-source simulators for robotics, V-REP, Gazebo and ARGoS, are thoroughly analysed and compared. While they all allow for programming in C++, they also represent clear alternatives when it comes to the trade-off between complexity and performance. Attention is given to their built-in features, robot libraries, programming methods and the usability of their user interfaces. Benchmark test results are reported in order to identify how well the simulators can cope with environments of varying complexity. The richness of features of V-REP and the strong performance of Gazebo and ARGoS in complex scenes are highlighted. Various usability issues of Gazebo are also noted.